PROSES KOGNITIF DALAM UNGKAPAN METAFORIS - deli - Nirmala (Master Program in Linguistics, Diponegoro University, 2014)
PROSES KOGNITIF DALAM UNGKAPAN METAFORIS Deli Nirmala deliundip@gmail.com Abstract Speech is produced through cognitive or psychological process, physiological process, and physical process (de Saussure, 1959). The cognitive process is the focus of this study especially in producing metaphorical expressions. This paper is trying to elaborate how the cognitive process happens when someone is producing metaphorical expressions. The data used for explaining the cognitive process are the metaphorical expressions found in bahasa Indonesia. The data were collected randomly from the sources like conversation, news, or bahasa Indonesia used in Indonesian newspapers. The method used is observation and intuition. To analyze, I used identity method, distributional method, and reflective-introspective methods. The result shows that the cognitive process in producing metaphorical process is done by using associative strategies by showing the correspondences between the source concept and the target concept. The correspondences found are those in embodied experiences, characters, functions, characteristics, and strenghts. Proses menghasilkan tuturan meliputi proses kognitif, fisiologis, dan fisik (de Saussure, 1959). Proses kogntif menjadi fokus dalam tulisan ini khususnya dalam proses menghasilkan ungkapan metaforis. Dalam tulisan ini, saya akan mencoba mengungkap bagaimana proses kognitif terjadi ketika seseorang menghasilkan ungkapan metaforis. Data yang dijadikan dasar dalam menjelaskan proses kognitif adalah ungkapan metaforis dalam bahasa Indonesia. Data dipilih secara random dari sumber berupa percakapan, berita, bahasa di surat kabar. Metode yang digunakan adalah metode observasi dan intuisi. Untuk menganalisis, saya menggunakan metode padan, distribusional, dan reflektif-introspektif. Hasil analisis menunjukkan bahwa proses kognitif dalam menghasilkan ungkapan metaforis dilakukan dengan strategi asosiatif dengan menunjukkan korespondensi antara konsep sumber dan konsep target. Korespondensi yang ditemukan adalah korespondensi yang ditunjukkan dalam pengalaman yang dialami tubuh, sifat, fungsi, ciri, dan kekuatan. Key Words:cognitive process, associative strategies, conceptual correspondences, metaphorical expressions